The system of horizontal fiscal equalization in the context of ensuring the implementation of the principles of unity and fairness of the budget system of Ukraine - N. Yaroshevych; I. Kondrat (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка)
The article is dedicated to defining the peculiarities of the system of horizontal fiscal equalization and substantiating the proposal for its improvement in terms of ensuring the implementation of the principles of equality and fairness of the budget system of Ukraine. The tax capacity index and reverse and basic grants were calculated for 1439 municipalities of Ukraine for 2022, taking into account the possible inclusion of the Kyiv city budget in the horizontal fiscal equalization system. This index is also computed for 2023 based on the population of territorial communities as of the beginning of 2022. It has been established that the exclusion from the equalization system of municipalities with the highest tax potential artificially increases the tax capacity of all other municipalities, thereby reducing the amount of the basic grant for grant recipients, and reduces their ability to fulfill responsibilities without attracting debt financing, and exacerbates the already significant development disparities between the capital and the regions. The involvement of the Kyiv city budget in the system of equalizing horizontal fiscal imbalances will satisfy the criteria of fairness and completeness in accordance with the principles of the budget system of Ukraine, significantly reduce the burden on the donors of the reverse grant and at the same time create a minimal (3% of the total need for basic grants) additional burden on the state budget. The comparison of the scheduled data for 2023 and the estimated data has shown that the amount of the estimated reverse grant is significantly higher than the scheduled amount of the grant for certain municipality, in particular for Kharkiv UTC (2.1 times) and Zaporizhzhia UTC (2.5 times), which suggests that the Ministry of Finance did not comply with the approved calculation methodology when planning interbudgetary transfers for 2023. The reasons for significant differences in the annual growth rates of PIT revenues (from 14.8% to 45%) to the budgets of different municipalities require additional research, as this makes the tax potential of a municipalities disproportionate to its grant need or grant potential. It is suggested to improve the system of horizontal equalization of fiscal imbalances in Ukraine by implementing EU legal norms into Ukrainian legislation, as a result of which personal income tax should be transferred to the local budget at the place of residence of the taxpayer, not at the place of registration of the tax agent.